Clinical Phenotypes of Tumors Invading the Rectosigmoid Colon Affecting the Extent of Debulking Surgery and Survival in Advanced Ovarian Cancer - Park, Soo Jin; Mun, Jaehee; Lee, Eun Ji; Park, Sunwoo; Kim, Sang Youn; Lim, Whasun; Song, Gwonhwa; Kim, Jae-Weon; Lee, Seungmee; Kim, Hee Seung (Frontiers in Oncology, 2021)
We classified clinical phenotypes based on tumor separability from the rectosigmoid colon and then evaluated the effect of these clinical phenotypes on surgical outcomes and prognosis of advanced ovarian cancer. We collected data of patients with stage IIIB-IVB disease who either underwent visceral segmental serosectomy (VSS) or low anterior resection (LAR) during maximal debulking surgery. All patients were divided into the following, according to the resection types of tumors involving the rectosigmoid colon: the focal (tumor-involved length <18 cm) and separable (FS) group that received VSS, the focal and inseparable (FI) that received LAR, or the diffuse (tumor-involved length ≥18 cm) group (D) that also received LAR. A total of 83 patients were included in FS (n=44, 53%), FI (n=18, 21.7%), and D (n=24, 25.3%) groups. FS and D groups with more extensive tumors were related to wider extent of surgery and more tumor infiltration except for bowels, whereas FI and D groups with more invasive tumors were associated with wider extent of surgery, more tumor infiltration to bowels, longer operation time, more blood loss, more transfusion, longer hospitalization, and higher surgical complexity scores. Moreover, FS and FI groups showed better progression-free survival than D group, whereas FS group demonstrated better overall survival than FI and D groups. Clinical phenotypes based on tumor separability from the rectosigmoid colon may depend on tumor invasiveness and extensiveness in advanced ovarian cancer. Moreover, these clinical phenotypes may affect surgical outcomes and survival.